Advancements in culture technology of adipose-derived stromal/stem cells: implications for diabetes and its complications - Shi, Yinze; Yang, Xueyang; Min, Jie; Kong, Wen; Hu, Xiang; Zhang, Jiaoyue; Chen, Lulu (Frontiers in Endocrinology, 2024)
Stem cell-based therapies exhibit considerable promise in the treatment of diabetes and its complications. Extensive research has been dedicated to elucidate the characteristics and potential applications of adipose-derived stromal/stem cells (ASCs). Three-dimensional (3D) culture, characterized by rapid advancements, holds promise for efficacious treatment of diabetes and its complications. Notably, 3D cultured ASCs manifest enhanced cellular properties and functions compared to traditional monolayer-culture. In this review, the factors influencing the biological functions of ASCs during culture are summarized. Additionally, the effects of 3D cultured techniques on cellular properties compared to two-dimensional culture is described. Furthermore, the therapeutic potential of 3D cultured ASCs in diabetes and its complications are discussed to provide insights for future research.